US climate change policy and the power sector - Robinson, D (Oxford Institute for Energy Studies, 2014)
On 2 June 2014 the US Environmental Protection Agency (EPA) published its proposed performance standards to reduce CO2 emissions from existing power stations. In 2012, these stations accounted for about 38.5% of US energy-related CO2 emissions, chiefly from coal. To date, the EPA proposal is the most substantial federal policy initiative aimed at reducing CO2 emissions in the US. However, other developments will also influence CO2 emissions from the power sector. In this paper, David Robinson places the proposed EPA regulations into their wider political and sectorial context. He analyses four determinants of the demand for coal and gas in the power sector, as well as the resulting CO2 emissions: the relative price of coal and natural gas; electricity demand; renewable power; and EPA regulations. There are four messages. First, reductions in CO2 emissions from the US power sector are likely to be modest, at least from a European perspective. Coal and natural gas will together continue to provide over 60 per cent of US electricity until at least 2030. Second, achieving EPA objectives for CO2 emissions reduction will be difficult, which partly explains why the targets are modest. There are barriers to reducing coal-based generation in the US, including the relatively low cost of coal and strong political support for coal in many states. Third, while the market share for natural gas will grow, its market in the power sector will be limited by rising natural gas prices, growth of renewables and flat or declining electricity demand. Finally, absence of bipartisan support for federal action to tackle climate change raises doubts about the successful implementation of EPA regulations and weakens US credibility in global climate negotiations.